Finance and Development, September 2007. (Finance and Development; Finance and Development, 2007)
The September 2007 issue of F and D looks at the growth of cities and the trend toward urbanization. Within the next year, for the first time in history, more than 50 percent of the world's population will be living in urban rather than rural areas. What are the economic implications of this urban revolution? Economists generally agree that urbanization, if handled well, holds great promise for higher growth and a better quality of life. But as the lead article tells us, the flip side is also true: if handled poorly, urbanization could not only impede development but also give rise to slums. Other articles in this series look at poverty as an urban phenomenon in the developing world and the development of megacities and what this means for governance, funding, and the provision of services. Another group of articles discusses the challenge of rebalancing growth in China. 'People in Economics' profiles Harvard economist Robert Barro; 'Country Focus' looks at the challenges facing Mexico, and 'Back to Basics' takes a look at real exchange rates.